Management Of Individual Based Learning of Guidance And Counseling at SMK Dr. Tjipto Ambarawa - Ervanawati, Narti Nunung (2012)
The objective of this research is to know how is the management of guidance and counseling based individual learning at SMK Dr. Tjipto Ambarawa. It takes tree subfocuses, namely how is the characteristic of structure and the organizational of guidance and counseling based individual learning and also how is the characteristics of interaction the guidance and counseling structure based individual learning in SMK Dr. Tjipto Ambarawa, and how is the actualization of guidance and counseling at SMK Dr. Tjipto Ambarawa. This is a qualitative research which a descriptive approach. It takes some informants or sources who directly involved to the guidance and counseling service, such as the headmaster, the vice-headmaster of students affairs, counselors, homeroom teachers, the teachers, the staff of administration, and also the students. In collecting the data, the researcher uses the method, namely observation, documentation, and deep interview. The characteristics of the structure and the organizational of guidance and counseling service in SMK Dr. Tjipto Ambarawa show that the structure involves the roles of some school personnels, such as the headmaster, the vice- headmaster of students affairs, the guidance and counselors, homeroom teachers, the teachers, the staff of administration. The headmaster has responsibility to all activities of guidance and counseling service, then he delegates this to the vice-headmaster of students affairs. Then the counselors focus on guiding both individual and also group of students. The counselors collaborate with the homeroom teachers, the homeroom teachers focus on giving the base of guidance which is done classically, do the service of orientation, information, group guidance, and also applied instrumentation. T he characteristics of client counselor interaction in guiding and counseling service in SMK Dr. Tjipto Ambarawa has run and organized well, showed from the fields and kinds of services given to the students.